PELAKSANAAN PROGRAM PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) MAHASISWA PENDIDIKAN KIMIA UNISKA MAB BANJARMASIN DI MASA PANDEMIC COVID-19 - GUSTI HADIATUS SOLEHAH; NOVRIAN DONY; NOVI RAHMAWANTI (LP2MTBM MAKARIOZ, 2022)
This article describes the implementation of the School Field Introduction (PLP) program for Chemistry Education students at the Islamic University of Kalimantan, MAB Banjarmasin. This study aims to describe the implementation of PLP in the limited face-to-face learning period (limited PTM) using descriptive qualitative methods using PLP student respondents. Sources of data in the form of observations, documentation, and interviews. Reliability using extended observations and triangulation. This program is carried out for 2 months starting from October to November 2021. This program is carried out right when limited face-to-face learning (limited PTM) is implemented in a high school in South Kalimantan. During those 2 months, there was a change in the duration of learning from 1 hour meeting (JP) for 22.5 minutes, changing to 45 minutes. During the learning activities carried out simultaneously both online and face-to-face in class. Although the PLP guide was made for normal conditions, the competencies and mastery expected in this activity were well achieved.